Under treatment of pneumonia among children under 5 years of age in a malaria-endemic area: population-based surveillance study conducted in Manhica district- rural, Mozambique. (July 2015) - Acácio, Sozinho; Verani, Jennifer R.; Lanaspa, Miguel; Fairlie, Tarayn A.; Nhampossa, Tacilta; Ruperez, Maria; Aide, Pedro; Plikaytis, Brian D.; Sacoor, Charfudin; Macete, Eusebio; Alonso, Pedro; Sigaúque, Betuel
Highlights: We assessed the clinical management of >60, 000 episodes of child pneumonia. In peripheral areas only 70% of severe pneumonia cases were appropriately managed. Less than half of non-severe pneumonia cases were correctly prescribed antibiotics. The major risk factor for failure to treat pneumonia was clinical malaria diagnosis. Better tools to distinguish between child pneumonia and malaria are needed. Summary: Background: Integrated Management of Childhood Illness (IMCI) guidelines were developed to decrease morbidity and mortality, yet implementation varies across settings. Factors associated with poor adherence are not well understood. Methods: We used data from Manhiça District Hospital outpatient department and five peripheral health centers to examine pneumonia management for children <5 years old from January 2008 to June 2011. Episodes of IMCI-defined pneumonia (cough or difficult breathing plus tachypnea), severe pneumonia (pneumonia plus chest wall in-drawing), and/or clinician-diagnosed pneumonia (based on discharge diagnosis) were included. Results: Among severe pneumonia episodes, 96.2% (2, 918/3, 032) attended in the outpatient department and 70.0% (291/416) attended in health centers were appropriately referred to the emergency department. Age<1 year, malnutrition and various physical exam findings were associated with referral. For non-severe pneumonia episodes, antibiotics were prescribed in 45.7% (16, 094/35, 224). Factors associated with antibiotic prescription included age <1 year, abnormal auscultatory findings, and clinical diagnosis of pneumonia; diagnosis of malaria or gastroenteritis and pallor were negatively associated with antibiotic prescription. Conclusion: Adherence to recommended management of severe pneumonia was high in a hospital outpatient department, but suboptimal in health centers. Antibiotics were prescribed in fewer than half of non-severe pneumonia episodes, and diagnosis of malaria was the strongest risk factor for incorrect management.